Characterizations of Anisotropic Superconductivity in (BiSe)1+δNbSe2. Issue 1 (1st August 2022) - Matsuzawa, S; Pyon, S; Tamegai, T
Abstract: Anisotropy of superconductivity in misfit layered compounds (BiSe)1+δ NbSe2 was studied. We synthesized single crystals of (BiSe)1+δ NbSe2 using CsCl/KCl flux method. There existed two phases with different T c depending on the starting composition δ, although their structures were almost unaffected by changing δ. Anisotropy of the upper critical field was determined by magneto-resistance measurements with various out-of-plane and in-plane field angles. The out-of-plane anisotropy of H c2 showed a cusp-like behavior for fields close to ab -plane similar to that predicted by 2D Tinkham model. Furthermore, a clear two-fold symmetry was observed in the in-plane angular dependence of H c2 .